The Prince Diponegoro’s war strategy from the perspective of the Indonesia total war strategy - Dadi Rusyadi; Deni DAR; Wayan Nuriada (Strategi Perang Semesta, 2022)
This article will be focused on Prince Diponegoro’s War Strategy that implemented Total War Strategy through Guerilla Warfare tactic. The purpose and objectives of this article are analyzing the Prince Diponegoro’s War Strategy as the form of People’s Total War to be comprehended as the Indonesia’s total war strategy in facing threats so the readers will gain knowledge and deep information regarding the implementation of total war strategy. The qualitative method was conducted to create this article through historical research approach in designing the content of this article. The Total War theory was also implemented on this article. Based on the research result, it was found that the Indonesian War conducted by Prince Diponegoro is essentially a picture of the People’s total War which are not only carried out by taking up arms, but also engaged in political, social, economic, and cultural fields. The Total War Strategy has applied by fighters both in armed struggle, which Total War values characterized by: populist, territorial, the total, has been embedded in every breath of struggle. Whole community participation in accordance with their respective roles, and empowering all resources maximum national power to be further combined with military power, become a form of "totality" that is powerful in dealing with various forms of threats. From the history of the Indonesian War by Prince Diponegoro which gave birth to the Total War concept, has demonstrated and proven that the involvement of all components of the nation, both military and civilian (non-military) have an important role in accordance with their respective fields.